1
$\begingroup$

Using Fermat's little theorem:

$(-6^{20} \cdot 5^{70})^{130}\equiv 1 \pmod{131}$

$-6^{2600} \cdot 5^{9100} \equiv 1 \pmod{131}$

I'm a bit stuck on where to go after this since I haven't really dealt with these sort of situations before however I feel like the answer is pretty simple to find from this step. All i'm asking for is a point in the right direction.

$\endgroup$
3
$\begingroup$

Use the fact that $5^3 \equiv - 6 \pmod{131}$. Then you have

$$-6^{20}\cdot 5^{70} \equiv (5^3)^{20}\cdot 5^{70} \equiv 5^{130} \equiv 1 \pmod{131}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.